A review on electronic nose for diagnosis and monitoring treatment response in lung cancer. (1st April 2023) - Vadala, Rohit; Pattnaik, Bijay; Bangaru, Sunil; Rai, Divyanjali; Tak, Jaya; Kashyap, Seetu; Verma, Umashankar; Yadav, Geetika; Dhaliwal, RS; Mittal, Saurabh; Hadda, Vijay; Madan, Karan; et al.
Abstract: Lung cancer is one of the common malignancies with high mortality rate and a poor prognosis. Most lung cancer cases are diagnosed at an advanced stage either due to limited resources of infrastructure, trained human resources, or delay in clinical suspicion. Low-dose computed tomography has emerged as a screening tool for lung cancer detection but this may not be a feasible option for most developing countries. Electronic nose is a unique non-invasive device that has been developed for lung cancer diagnosis and monitoring response by exhaled breath analysis of volatile organic compounds. The breath-print have been shown to differ not only among lung cancer and other respiratory diseases, but also between various types of lung cancer. Hence, we postulate that the breath-print analysis by electronic nose could be a potential biomarker for the early detection of lung cancer along with monitoring treatment response in a resource-limited setting. In this review, we have consolidated the current published literature suggesting the use of an electronic nose in the diagnosis and monitoring treatment response of lung cancer.